2014
DOI: 10.1590/1414-431x20143767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different frequencies of transcutaneous electrical nerve stimulation on venous vascular reactivity

Abstract: Transcutaneous electrical nerve stimulation (TENS) is a type of therapy used primarily for analgesia, but also presents changes in the cardiovascular system responses; its effects are dependent upon application parameters. Alterations to the cardiovascular system suggest that TENS may modify venous vascular response. The objective of this study was to evaluate the effects of TENS at different frequencies (10 and 100 Hz) on venous vascular reactivity in healthy subjects. Twenty-nine healthy male volunteers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Four pairs of electrodes for TENS (6805-D model, Shantou City Medical Equipment Co., Ltd., Shantou City, China) were placed on the acupoints and fixed with adhesive tape. Treatment frequency was set for 2Hz according to the study by Franco et al 37 Electrodes of the same pair can only be connected at the same side to avoid direct contact across the body. In the control group (placebo acu-TENS), the devices were set as mentioned for the active treatment group, but no electrical current was applied.…”
Section: Intervention Programmentioning
confidence: 99%
“…Four pairs of electrodes for TENS (6805-D model, Shantou City Medical Equipment Co., Ltd., Shantou City, China) were placed on the acupoints and fixed with adhesive tape. Treatment frequency was set for 2Hz according to the study by Franco et al 37 Electrodes of the same pair can only be connected at the same side to avoid direct contact across the body. In the control group (placebo acu-TENS), the devices were set as mentioned for the active treatment group, but no electrical current was applied.…”
Section: Intervention Programmentioning
confidence: 99%
“…This sympathetic innervation by postganglionic nerve fibers facilitates vasoconstriction by the release of norepinephrine and subsequent smooth muscle contraction (Fischer et al 1993). Electrical stimulation of sympathetic nerve fibers can promote release of norepinephrine and vasoconstriction as evidenced by several studies investigating frequency ranges similar to that of the microcurrent study device (Franco et al 2014;Malm 1973;Mandel et al 2013). Vasoconstriction of arterioles and venous vessels, in the context of sinonasal inflammation, results in smaller vessel diameter, reduced edema and extravasation of inflammatory immune cells, as well as less nasal resistance to air flow, all of which can contribute to reduced symptom m severity and decongestant effects (Naclerio et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a further study has shown that the application of low frequency TENS in the ganglion region is more effective to increase vasodilation in lower limbs when compared to the application of TENS in acupunture points or with the control group, in healthy subjects, proving the change in sympathetic activity [24]. These changes in the vascular tone caused by TENS might stem from the interaction of the endothelial cell layer and physical or chemical stimuli that share a functional antagonism with the sympathetic nervous system in maintaining blood vessel tone, by the release of substances that affect the vascular tonus [25].…”
Section: Discussionmentioning
confidence: 94%